2019
DOI: 10.3389/fchem.2019.00266
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous WO3 Nanofibers With Crystalline Framework for High-Performance Acetone Sensing

Abstract: Semiconducting metal oxides with abundant active sites are regarded as promising candidates for environmental monitoring and breath analysis because of their excellent gas sensing performance and stability. Herein, mesoporous WO 3 nanofibers with a crystalline framework and uniform pore size is successfully synthesized in an aqueous phase using an electrospinning method, with ammonium metatungstate as the tungsten sources, and SiO 2 nanoparticles and polyvinylpyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 66 publications
0
18
0
1
Order By: Relevance
“…However, a distinctive polycrystalline surface morphology of the fiber with the diameter of individual fibers being in the range of 285-290 nm, which is composed of densely packed grains of 50-100 nm size, is observed for white WO 3−x NFs (Figure 2d). [17] During the preparation of a fully oxidized white WO 3 NFs, we carried out the high-temperature calcination under O 2 atmosphere. As demonstrated in Figure 2e,f, severe grain growth of thermally sintered particles occurred.…”
Section: Resultsmentioning
confidence: 99%
“…However, a distinctive polycrystalline surface morphology of the fiber with the diameter of individual fibers being in the range of 285-290 nm, which is composed of densely packed grains of 50-100 nm size, is observed for white WO 3−x NFs (Figure 2d). [17] During the preparation of a fully oxidized white WO 3 NFs, we carried out the high-temperature calcination under O 2 atmosphere. As demonstrated in Figure 2e,f, severe grain growth of thermally sintered particles occurred.…”
Section: Resultsmentioning
confidence: 99%
“…The nanosheets synthesized for 6 h (NS-6) had the highest sheet area, leading to a 10 times higher response than those synthesized for 2 h and 24 h. They concluded that controlling the crystal facet of a nanomaterial can enhance the sensing characteristics without the requirement of noble metal decoration. Xu et al synthesized WO 3 nanofibers using SiO 2 nanoparticles and polyvinylpyrrolidone (PVP) as sacrificial templates, ammonium paratungstate as a tungsten precursor, and water as a solvent [ 96 ]. WO 3 nanofiber-based sensors were found to show magnificent acetone-sensing capabilities with a low detection limit, fast response and recovery, and high stability.…”
Section: Sensing Methodologies For Breath Analysismentioning
confidence: 99%
“…Luo et al found the sensitivity of porous WO 3 is 66 % higher than that of nonporous WO 3 and exhibit much faster response time. [77] The crystal facet engineering, elemental doping, and creating heterojunctions promote the reaction kinetics. [6a] The porous framework of WO 3 provides strong support to anchor metal nanoparticles.…”
Section: Sensingmentioning
confidence: 99%